Covid-19 Pandemic and Vaccine - Shah, Santosh (Journal of Universal College of Medical Sciences, 2021)
COVID-19, caused by SARS-CoV-2, was first reported in Wuhan, in December 2019 and later spread globally. The World Health Organization (WHO) declared the outbreak a Public Health Emergency of International Concern (PHEIC) on 30 January and a pandemic on 11 March 2020.1 In Nepal, the first case was registered on 3rd January 2020. Since then, there have been 591,494 confirmed cases of COVID-19 with 7,990 deaths.2 In the second wave of Covid-19, South Asia seems to have turned into the epicentre as most of the countries in the region, including India, Nepal, Bangladesh, and Pakistan have been badly infected by the coronavirus. Instead of being controlled, the situation is getting more flared up as each day passes. Of late, the situation in Nepal is gradually becoming alarming as two out of five people tested return positive. Subsequently, Nepal started to face shortage of oxygen, ventilators, and ICU facilities required for the treatment of severe cases. Medicines like Remdesivir and other medical equipment are sold at exorbitant prices.